Measuring Self-Efficacy in the Context of Pediatric Diabetes Management: Psychometric Properties of the Self-Efficacy for Diabetes Scale. (4th July 2017) - Van Allen, Jason; Noser, Amy E; Littlefield, Andrew K; Seegan, Paige L; Clements, Mark; Patton, Susana R
Abstract: Objective: The Self-Efficacy for Diabetes Scale (SED) is a widely used measure of diabetes-specific self-efficacy with three subscales: diabetes-specific self-efficacy (SED-D), medical self-efficacy (SED-M), and general self-efficacy (SED-G). The present study examined the factor structure and construct validity of the SED in 116 youth, aged 10–16 years (13.60 ± 1.87), with type 1 diabetes mellitus. Methods: Confirmatory factor analysis (CFA) was used to examine the factor structure of the SED. Correlational and regression analyses examined relations between subscales and select outcomes. Results: CFA of the original three-factor structure provided a poor fit to the data. Factor models using rescaled items were tested. Results provided preliminary evidence for the SED-D as an independent one-factor model, and for a reduced one-factor model. Significant associations were found between the SED subscales, responsibility for diabetes management, and glycated hemoglobin. Conclusions: Results provide limited support for the SED-D as a reliable and valid measure of diabetes-specific self-efficacy.